(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The aim of this work was to develop, implement and use a computational framework to study and address the major outstanding issues in digital chest imaging in order to expedite its introduction into routine clinical use.The information about X-rays and how they are produced are discussed, as well as some applications of X-rays in medicine, as well as their risks and how to prevent them. This was done in the first chapter of this research.As for the second chapter, the chest area and its sections (heart, lungs, diaphragm, middle) were selected, and multiple samples (X-ray images) were selected for each organ, and some information that contributes to creating a work environment was identified. specified. also pointed out.In the third chapter, the previously reviewed samples are discussed and explained in detail As well as reviewing the problems facing the technician and how to overcome them.